Chapter Elementi stilistici decameroniani nel Pecorone di ser Giovanni - Esposito, Nicola (Studi e saggi, 2022)
In the history of scholarship on vernacular style, rhetoric, and prose rhythm, very little space has been given to 14th-century Tuscan short stories writers, such as Ser Giovanni, Franco Sacchetti, and Giovanni Sercambi. This article analyzes Ser Giovanni's Pecorone with the aim of individuating stylistic, rhetorical, and rhythmic elements and of understanding their relationship with its model, Giovanni Boccaccio's Decameron. Although Ser Giovanni did not have a direct knowledge of the artes dictaminis, the article shows how his deep reading of Boccaccio's Decameron permitted him to recognize and put to use many of the rhetorical expedients he found in it.